Interferon gamma-inducible protein 16 in primary Sjögren’s syndrome: a novel player in disease pathogenesis? - Alunno, Alessia; Caneparo, Valeria; Carubbi, Francesco; Bistoni, Onelia; Caterbi, Sara; Bartoloni, Elena; Giacomelli, Roberto; Gariglio, Marisa; Landolfo, Santo; Gerli, Roberto (Arthritis research & therapy, 2015)
There is evidence that interferon is involved in the pathogenesis of primary Sjögren's syndrome (pSS). The interferon-inducible IFI16 protein, normally expressed in cell nuclei, may be overexpressed, mislocalized in the cytoplasm and secreted in the extracellular milieu in several autoimmune disorders. This leads to tolerance breaking to this self-protein with consequent development of anti-IFI16 antibodies. The aim of this study was to identify the pathogenic and clinical significance of IFI16 and anti-IFI16 in pSS. IFI16 and anti-IFI16 were assessed in the serum of 67 pSS patients and over 100 healthy donors by enzyme-linked immunosorbent assay. IFI16 was also evaluated by immunohistochemistry in minor salivary glands of 15 pSS patients and 10 subjects with sicca symptoms but without any clinical, serological or histological features of pSS. pSS patients display higher serum levels of both IFI16 and anti-IFI16 compared to healthy donors. IFI16 concentration was directly correlated with disease duration and focus score and inversely correlated with age at diagnosis. Moreover, IFI16 positivity was associated with concurrent positivity for rheumatoid factor. Interestingly, the direct correlation between IFI16 positivity and focus score was independent of disease duration and age at diagnosis. pSS minor salivary glands display marked expression and cytoplasmic mislocalization of IFI16 by acinar and ductal epithelial cells as well as infiltrating lymphocytes and peri/intralesional endothelium compared to minor salivary glands with normal architecture or nonspecific chronic sialadenitis. Within the mononuclear cell infiltrate, IFI16 expression appears to parallel the distribution of T lymphocytes. Our data suggest that the IFI16 protein may be involved in the pathogenesis of glandular inflammation occurring in pSS.